(untitled) (Journal of Asian Development Studies, 2025)
This study addresses a significant gap in the literature by investigating the impact of public debt and green technology and other variables on energy consumption in Pakistan using 33 years’ time series data from 1990-2023 sourced from the World Bank, OECD, IMF, and ICRG and employing statistical techniques such as Correlation matrix and ARDL model to identify long-term relationship between public debt, green technology and energy consumption. The findings reveal public debt and natural resources exert positive impact on energy consumption while green technology, institutional quality and GDP growth have negative impact on it in the long-term. This suggests that while green tech contributes to sustainability and indicates pathways to reduce energy production costs through enhanced efficiency and structural optimization, it does not lead to reduce aggregate energy consumption immediately. These findings imply that for developing economies like Pakistan, green technology, supported by prudent debt management, is vital for long-term energy sustainability despite its complex short-term effects on consumption.